Trouble in Paradise - Parker, Robert B., 1932-2010 (Berkley, 2007)
A gang of robbers lands on an island in Massachusetts and they proceed to rob its wealthy inhabitants. First, they destroy the bridge to the mainland. Jesse Stone, the alcoholic chief of police in Paradise, a town on the mainland, organizes a relief operation. By the author of Night Passage.